2018
DOI: 10.1177/2309499018760132
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty for the treatment of acute complex proximal humeral fractures: Influence of greater tuberosity healing on the functional outcomes

Abstract: In spite of expecting good functional outcome with low complication rate after RSA for acute PHFs, the influence of greater tuberosity healing on shoulder function could not be demonstrated. The presence of comorbidities, but not age or gender, negatively influenced the healing of the greater tuberosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 23 publications
3
43
1
12
Order By: Relevance
“…As for the second objective of the study, tuberosity healing occurred in 76.3% of the patients. This percentage is in line with more recent studies, 22 29 30 and it is superior to older works. Boileau et al 28 describe a higher healing rate, of 84%, arguing that tuberosity healing in fractures submitted to RSP is a reproducible procedure even in the elderly.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As for the second objective of the study, tuberosity healing occurred in 76.3% of the patients. This percentage is in line with more recent studies, 22 29 30 and it is superior to older works. Boileau et al 28 describe a higher healing rate, of 84%, arguing that tuberosity healing in fractures submitted to RSP is a reproducible procedure even in the elderly.…”
Section: Discussionsupporting
confidence: 92%
“…In a prospective study evaluating patients with complex PHF undergoing RSP, Bufquin et al 15 concluded that tuberosity non-healing does not necessarily lead to a poor outcome. Torrens et al 22 stated that clinical results are superimposable, not depending on tuberosity healing. Reverse shoulder prostheses are based on the classical principles of the prosthesis developed by Grammont: a) a semi-constrictive fixed point (fulcrum) prosthesis enabling the deltoid to elevate the arm in a way that does not require rotator cuff action, and b) a lower, medialized center of rotation, which enables deltoid extension and thus decreases the force required for arm abduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening, 277 documents were excluded, thus including 46 for full-text review. Of these 46 references, 25 were excluded and 21 studies were included in the final evidence tables [18][19][20][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Table 1 shows the level of evidence of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence and severity of notching were high with first-generation RTSA, but the scapular notch rate in fracture patients tended to be lower than that reported for cuff-deficient patients. 37 The potential progression of scapular notching is worrisome, although the long-term effects of this finding have yet to be elucidated. Severe erosions of the scapular neck causing glenoid component loosening are infrequent, particularly with newer RTSA designs.…”
Section: Hemiarthroplasty Vs Reverse Total Shouldementioning
confidence: 99%